Increasing Kedai Kopi Nadi's Brand Awarness To Its Target Market Through Instagram - Jessica Jessica (Institute of Research and Community Outreach - Petra Christian University, 2022)
This creative thesis is made to solve the problem that Kedai Kopi Nadi has namely low brand awareness. This cafe has been around for more than a year, but few people know about it. In fact, Kedai Kopi Nadi’s ambiance and price of the products can beat other cafes such as Montana, Zona Nyaman, and Kopi Nusantara. Unfortunately, the only social media they have, namely Instagram, is not used properly so it becomes ineffective for marketing. With a target market of university students ranging from 18 to 25 years old, showing off Kedai Kopi Nadi’s USP on Instagram is effective to attract them. Kedai Kopi Nadi has several USPs that can be highlighted on the Instagram content. Its strengths are the product price, the ambiance or atmosphere of the cafe, and the product menu. Not only that, the writer collected answers from Kedai Kopi Nadi’s customers and target market to create content that was suitable for Kedai Kopi Nadi. The writer got more information on what to highlight in the content by doing it. By making the Instagram content, the writer aims to introduce the brand widely to the audience and to increase Kedai Kopi Nadi’s brand awareness.